Effects of Exposure to Mild Hyperbaric Oxygen on DSS-Induced Colonic Inflammation and Diarrhea in Rats - Takemura, Ai (J Inflamm Res, 2019)
PURPOSE: In rodents, dextran sulfate sodium (DSS)-induced diarrhea and colonic inflammation have similar symptoms to those of ulcerative colitis in humans. We examined the effects of exposure to mild hyperbaric oxygen (MHO) at an atmospheric pressure of 1317 hPa with 40% oxygen on DSS-induced diarrhea and colonic inflammation in rats. METHODS: Five-week-old male Kyoto Apc Delta (KAD) rats (n = 12) were administered 2% DSS through drinking water for 1 week. Subsequently, DSS-treated male rats were not subjected to any further treatment (n = 6) or exposed to MHO (n = 6) for 2 weeks. Age-matched KAD rats not subjected to DSS treatment or exposed to MHO were used as the control group (n = 6). RESULTS: Control rats did not exhibit diarrhea and colonic inflammation. However, DSS-treated rats exhibited diarrhea and colonic inflammation, regardless of exposure to MHO. Exposure to MHO for 2 weeks led to decreased incidence of diarrhea in DSS-treated rats (p < 0.05). Exposure to MHO had no effect on colonic inflammation in DSS-treated rats (p = 0.12). CONCLUSION: Exposure to MHO for 2 weeks can improve diarrhea but cannot attenuate colonic inflammation, possibly due to the short exposure duration (2 weeks) used in this study.